2015
DOI: 10.1515/rjim-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

P Wave Signal-Averaged Electrocardiography in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The patients with acute exacerbation of COPD but no apparent cardiac disease have a higher incidence of supraventricular arrhythmias. P-wave SAECG analysis and ALP detection have little value in the arrhythmic risk evaluation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…P-wave duration and PQ interval were also reported to be risk factors for AF development in patients with P pulmonale, and P-wave duration is highly correlated with PQ interval >150 ms [31]. On the contrary, Buzea et al reported that in patients with acute COPD exacerbations, P-wave signal averaged electrocardiography (SAECG) analysis and atrial late potentials detection seem to have little value in the arrhythmic risk evaluation [32].…”
Section: Pathophysiological Mechanisms Implicating Chronic Obstructive Pulmonary Disease In Atrial Fibrillationmentioning
confidence: 99%
“…P-wave duration and PQ interval were also reported to be risk factors for AF development in patients with P pulmonale, and P-wave duration is highly correlated with PQ interval >150 ms [31]. On the contrary, Buzea et al reported that in patients with acute COPD exacerbations, P-wave signal averaged electrocardiography (SAECG) analysis and atrial late potentials detection seem to have little value in the arrhythmic risk evaluation [32].…”
Section: Pathophysiological Mechanisms Implicating Chronic Obstructive Pulmonary Disease In Atrial Fibrillationmentioning
confidence: 99%
“…P-wave signal-averaged electrocardiography, atrial late potentials (ALP), and abnormal intra-P-wave potentials could detect patients at risk of supraventricular arrhythmias, especially atrial ibrillation [42,43]. ALP originates from areas of delayed and heterogenous conduction within the atrial myocardium, responsible for the occurrence of AF [44].…”
Section: P-wave Potentialsmentioning
confidence: 99%
“…There is no consensus about the cut-of point for FPD, which was 121 ms in hypertensive patients Auriti et al [48], 124 ms in patients in sinus rhythm, 136 ms in hypertensive patients with a history of atrial ibrillation, 132 ms in patients with COPD, and 155 ms in several other studies [43,45,46,49], diferences related to diferent averaging and iltering methods [45].…”
Section: P-wave Potentialsmentioning
confidence: 99%
See 1 more Smart Citation